STATUS AND ECOLOGY OF GOULD'S TURKEY IN THE PELONCILLO MOUNTAINS OF NEW MEXICO - Thomas D. Potter; Sanford D. Schemnitz; William D. Zeedyk (Wildlife Society Bulletin)
Abstract: Two reconnaissance surveys in April and June of 1982 verified the presence of Gould's turkeys (Meleagris gallopavo mexicana) in the Animas, San Luis, and Peloncillo Mountains in Hidalgo County, southwestern New Mexico. An intensive 12‐month field study was conducted in the Coronado National Forest portion of the Peloncillo Mountains in 1983 to determine population numbers, distribution, habitat requirements, and possible limiting factors. A total of 16 Gould's turkeys was located in the study area. Four of these were lost to unknown causes in the spring. One hen hatched 6 poults, all of which survived through at least December. The main habitat of Gould's turkey is the Madrean Evergreen Woodland community, characterized by gray (Quercus grisea) and Emory oaks (Q. emoryi), alligatorbark juniper (Juniperus deppeanna), pinyon pine (Pinus cembroides), and Chihuahua pine (Pinus leiophylla) in the bottoms. Beargrass (Nolina microcarpa), manzanita (Arctostophyles pungens), and grama (Bouteloua spp.) grasses were key understory components. Fifteen roost sites were located, with 47 trees used. Two of these trees were Emory oak and the remainder were Chihuahua pine. Brood‐rearing occurred in the open rolling hills and wide bottoms on the eastern slope of the study area, where beargrass was important for escape cover. Juniper and manzanita berries were the 2 most utilized food items, based on a microhistological fecal analysis of 240 droppings gathered yearlong. Various mustard forbs were important in the early spring, and grass seedheads were utilized when available. Poaching, predation, overgrazing, firewood and beargrass harvesting, emigration, and hybridization with domestic turkeys are potential limiting factors of the Peloncillo population. Management recommendations included: livestock exclosures, water developments, more restrictive firewood and beargrass harvesting, and removal of the domestic turkeys.